Generation of Differentially Modified Microtubules Using In Vitro Enzymatic Approaches - Vemu, Annapurna; Garnham, Christopher P.; Lee, Duck-Yeon; Roll-Mecak, Antonina (Methods in Enzymology, 2014)
Tubulin, the building block of microtubules, is subject to chemically diverse and evolutionarily conserved post-translational modifications that mark microtubules for specific functions in the cell. Here we describe in vitro methods for generating homogenous acetylated, glutamylated, or tyrosinated tubulin and microtubules using recombinantly expressed and purified modification enzymes. The generation of differentially modified microtubules now enables a mechanistic dissection of the effects of tubulin post-translational modifications on the dynamics and mechanical properties of microtubules as well as the behavior of motors and microtubule-associated proteins.